Association between Serum Insulin and Interleukin-6 levels with Breast Cancer in Post-Menopausal Iraqi Women - Abd, Mohammed A.; Majeed ٍShaymaa A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Obesity rates are increasing day by day affecting all populations at different ages. The most prevalent kind of cancer among women worldwide is breast cancer, with increasing rates in the present time and the future. Substantial connections between obesity and breast cancer are demonstrated. Elevated circulating levels of insulin and interleukin-6 have a substantial link to obesity and breast cancer development. Objective: This study aimed to examine the serum levels of insulin and interleukin-6 in postmenopausal breast cancer patients and to study the connection between these biomarkers and breast cancer development. Method: In this research, 120 postmenopausal women actively participated: 30 had a body mass index of >30 kg/m2 diagnosed with breast cancer and considered as obese (group 1), 30 with a body mass index of <30 kg/m2 with breast cancer and considered as not obese (group 2), 30 had a body mass index of >30 kg/m2 who were healthy and were obese (group 3), and 30 participants with a body mass index of <30 kg/m2 were healthy and were not obese (group 4). Five millilitres of venous blood were provided by each individual. Insulin and interleukin-6 levels in the blood were measured using ELISA (enzyme-linked immunosorbent assay) kits. Results: Serum insulin levels were higher in the groups of obese participants (groups 1 and 3) than in the groups of non-obese participants (groups 2 and 4); serum levels of interleukin-6 were the lowest in the healthy control group without obesity (group 4). A substantial moderate correlation was found between body mass index and both insulin and interleukin-6. Postmenopausal breast cancer risk is increased with elevations of serum insulin and interleukin-6. Conclusions: Elevated levels of serum interleukin-6 and insulin were linked to higher body mass index. In addition, interleukin-6 elevated levels were linked to the cancer state of the non-obese patients. The risk of breast cancer increases with higher levels of circulating insulin and interleukin-6.